Potential antifungal activity of dioscorea daemona (ubi gadong) tuber extract against pyricularia grisea pathogen of rice blast disease / Neni Kartini Che Mohd Ramli and Khairun Nur Ali - Che Mohd Ramli, Neni Kartini; Ali, Khairun Nur (Universiti Teknologi MARA Cawangan Pahang, 2018)
Many of plants in Malaysia potentially can be used as bio fungicides. Dioscorea daemona(Ubi Gadong) has been used in traditional herbal medicine and as decoction in various areas for decades. Tuber extracts of this plant have also been reported to possess antifungal, antibacterial and antioxidant activities. Tuber crude extracts of D. daemona was consecutively separated into hexane, chloroform and methanol and screened for antifungal activities in vitro against Pyricularia grisea, pathogen of rice blast disease using well diffusion method on Potato Dextrose Agar. Results of this study showed that the methanol crude extract of D. daemona exhibited a very strong inhibitory activity against P. grisea with diameter of inhibition zone by 1.5cm (62.5% inhibition) at concentration 150,000ppm. Antifungal activities of most effective extracts were supported by the presence of chemical constituents such as alkaloids, saponin, flavonoids, terpenoids and phenol that were responsible for the antifungal activity. It could be inferred that methanol tuber extracts of D. daemonaat 150,000ppm concentration can serve as bio-fungicides against the growth of P. grisea